2018
DOI: 10.1007/s00464-018-6360-4
|View full text |Cite
|
Sign up to set email alerts
|

Defining the learning curve for transanal total mesorectal excision for rectal adenocarcinoma

Abstract: TA-TME is a complex technique that requires a minimum of 45-51 cases to reach an acceptable incidence of high-quality TME and lower operative duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 31 publications
4
105
2
Order By: Relevance
“…A recent study that defined proficiency in TaTME as high-quality TME (complete/near-complete mesorectal envelope, and negative distal and circumferential resection margin) showed a learning curve of at least 45-51 cases. 19 This finding is consistent with the results of a systematic review by Deijen and colleagues, which demonstrated that there is a difference in oncologic outcomes at high-volume (> 30 cases) and low-volume (< 30 cases) centres, with high-volume centres having a higher "complete" TME rate as well as a lower circumferential resection margin involvement and fewer major complications. 20 In another single-centre study, which assessed 138 patients operated on over a 5-year period, there was a substantial drop in major complications once a surgeon's experience exceeded 40 patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent study that defined proficiency in TaTME as high-quality TME (complete/near-complete mesorectal envelope, and negative distal and circumferential resection margin) showed a learning curve of at least 45-51 cases. 19 This finding is consistent with the results of a systematic review by Deijen and colleagues, which demonstrated that there is a difference in oncologic outcomes at high-volume (> 30 cases) and low-volume (< 30 cases) centres, with high-volume centres having a higher "complete" TME rate as well as a lower circumferential resection margin involvement and fewer major complications. 20 In another single-centre study, which assessed 138 patients operated on over a 5-year period, there was a substantial drop in major complications once a surgeon's experience exceeded 40 patients.…”
Section: Discussionsupporting
confidence: 89%
“…(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) 9(5)(6)(7)(8)(9)(10) IQR = interquartile range; TaTME = transanal total mesorectal excision. *Surgeons who were performing TaTME at the time of the survey.†Surgeons who were not performing TaTME at the time of the survey.…”
mentioning
confidence: 99%
“…A high rate of positive margins despite low tumour stage, the high rate of permanent stomas and perioperative morbidity may be indicative of suboptimal TaTME procedures. An unsupervised learning curve without proctoring, as shown by experienced single-port surgeons, takes over 40 procedures 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these positive results, it is also acknowledged that TaTME is a difficult technique and has a long learning curve with associated morbidity 10,11 . The international TaTME registry 3 and a systematic review 4 have shown that widespread adoption results in less favourable clinical outcomes than reported in the initial cohorts treated in expert centres.…”
Section: Introductionmentioning
confidence: 99%
“…Although the learning curve of taTME has not been fully clarified 7,49) , the skills are believed to be difficult to acquire and care should be taken to avoid serious complications, especially in the early learning stages 50) . Deijen et al in their study performed pooled-analysis and compared clinical outcomes between low-volume (< 30 cases) and high-volume ("30 cases) centers.…”
Section: Education and Trainingmentioning
confidence: 99%